Consensualidade como instrumento de legitimidade no processo antitruste sancionador brasileiro: considerações sobre o Acordo de Leniência - Pantoni, Roberta Alessandra (2012)
This work aimed at making a study on the \"Leniency Agreement\", a legal institute used in the course of administrative sanctioning procedures that investigate violations of the economic order, more specifically those which are linked to the formation of cartels . The analysis proposed here has surpassed the notion of the institute as a simple mechanism of evidence acquisition, going beyond. The investigation started from the perspective of its consensual nature in order to insert it in the current context of a greater democratization of Public Administration. To do so, it was made an analysis on some conceptual categories such as administrative procedure , public interest , democratic principle and legitimacy , as well as, a study of some implicit and explicit constitutional principles of the Public Administration legality, purpose, morality, impartiality and efficiency principles looking forward to reframing them in the context of the emerging Interventional State. Therefore, on the one hand, it was done an incursion on the constitutional and economic order, on the other, an analysis of the administrative processuality regarding the changes through which the administrative law has passed and is still passing. By using the deductive method and the documentary and bibliographical research techniques it was possible to verify that the Leniency Agreement , a consensual procedural mechanism, appears as a genuine legitimacy instrument on sanctioning brazilian antitrust procedure, once it makes practical an efficient state actioning in the pursuit for public interest satisfaction.